SIETE PERSONAJES EN BUSCA DE UN REMAKE: DE KUROSAWA A FUQUA, PASANDO POR STURGES - Dr. José M. LAVÍN,Dr. Álvaro JIMÉNEZ SÁNCHEZ,Dr. Jesús María NAVALPOTRO SÁNCHEZ-PEINADO, (Fonseca, Journal of Communication, 2023)
The current investigation tries to analyze the play of Seven samurai of Kurosawa (1956), the remake of Sturges (1960) and the Fuqua’s version of 2016.Nevertheless, there are more films based on the Japanese film, these two works were studied because they are considered the most relevant in the way of making contextualized adaptations in an occidental country and a determined historical and social moment.